Tropism of sheep lentiviruses for monocytes: susceptibility to infection and virus gene expression increase during maturation of monocytes to macrophages. - Gendelman, H E (1986)
Visna lentiviruses have a natural tropism for cells of the macrophage lineage of sheep and goats, but virus replication in these cells in vivo is restricted so that only small quantities of virus are produced. One restricting factor suggested in previous studies is that virus replication is dependent on the maturity of the cells: the more mature the cell, the less restrictive the replication of the virus. Since monocytes in peripheral blood are precursors of macrophages, we investigated the effect of cell maturation on virus replication under limited control conditions in vitro by inoculating blood leukocytes with virus and retarding the maturation of monocytes to macrophages during cultivation in serum-free medium. Using enzyme markers that identified the cells in their resting monocytic stage (peroxidase) and mature macrophage stage (acid phosphatase) along with quantitative in situ hybridization and immunocytochemistry with viral reagents to trace the efficiency of virus replication, we correlated virus replication with cell maturation. Only a few monocytes were susceptible to infection, and virus replication did not extend beyond a low level of transcription of viral RNA. In the acid phosphatase-positive, maturing macrophage, susceptibility of the cells to infection was increased and virus replication was greatly amplified to the level of translation of viral polypeptides. However, virus maturation was delayed by 3 days until further cell maturation had occurred. Thus, the entire life cycle of the virus, from its attachment to the target cell to its maturation in the cell, was dependent on the level of maturation/differentiation of the monocytic cell.